Rules that matter: limits to competition policy harmonisation in EU enlargement - Jan Overgaard Olesen; Ole Risager (Copenhagen Business School (CBS), Department of Economics, 2000)
This paper analyzes whether, and to what extent, the Danish 1, 5 and 10-year equity premia are predictable. We examine the predictive power of a comprehensive list of financial ratios, interest rates and so forth. The results show that the 5-year premium is predictable in the sense that the model explains a non-trivial proportion of the variability of the equity premium. Moreover, the model is good at predicting turning points in the premium. We also analyze the portfolio implications of the model and find that the model is useful in predicting the optimal return maximizing portfolio choice. Finally, the paper presents forecasts for the 5-year equity premium.
hdl:10398/7554
Keywords: G11; 330; equity premia; interest rates; portfolio choice; Denmark